Vascularized composite allotransplantation in children: what we can learn from solid organ transplantation. Issue 5 (October 2018) - McDiarmid, Sue V.
Abstract : Purpose of review: This review will focus on the lessons learned over several decades of solid organ transplantation in children, and their relevance to the emerging field of pediatric VCA. Particular attention will be focused on the risk–benefit ratio of immunosuppression as it applies to children receiving a life-enhancing transplant as compared with a life-saving transplant. Potential indications for pediatric VCA will be considered. Recent findings: The report in 2015 of the first child to receive a VCA, bilateral upper extremity grafts from a nonrelated deceased donor, is a seminal event. The case is unique in that the child was already immunosuppressed after a prior kidney transplant. Early graft function is excellent and cortical re-organization has been described. Summary: Although the risks of immunosuppression remain a formidable obstacle to the wider spread application of VCA for children, careful consideration of indications and outcomes for these innovative procedures, which have the potential to restore form and function not otherwise achievable, is warranted.